Implementasi Media Gambar Ilustrasi Naturalis dalam Meningkatkan Konsentrasi Belajar Anak - Fathor Rozi; Siti Rahayu (MANAZHIM, 2022)
This study aims to examine the implementation of Naturalist Illustrated Image Media towards the Concentration of Early Childhood Learning in Taman Posyandu (TP) Anak Shalih Karanganyar Paiton Probolinggo. The research method uses a qualitative type and a case study approach. The subjects of the study were students at Taman Posyandu (TP) Anak Shalih Karanganyar Paiton Probolinggo totaling 20 children. Data collection techniques through interviews, observation and documentation. Data retrieval techniques with snawball sampling, the data sources used are primary and secondary. Data analysis using Huberman miles analysis. The results showed that planning, implementing and evaluating the implementation of naturalist illustrated image media can increase the level of early childhood concentration in Taman Posyandu (TP). Shalih's son. The implication of this study is the need for continuity of guidance, monitoring, and evaluation by teachers of learning media used to determine the progress of children's learning concentration.